Close Reading with Paired Texts Secondary : Engaging Lessons to Improve Comprehension. - Rasinski, Timothy (Close Reading with Paired Texts., 2018)
Prepare middle school students for college and career with 12 close reading units designed to support content-area instruction and literacy development. Each unit includes text-dependent questions and paired fiction and nonfiction texts.